Regional Differentiation of Criminality in the Czech Republic - Rumlová, Denisa; Matěja, Zdeněk (Univerzita Pardubice, 2018)
The issue of regional development is closely related to the security of the region, because a region facing security problems is not usually able to provide conditions for the required level of development and living standard of the population. This paper deals with the issue of regional differentiation of crime in the Czech Republic. The aim of the contribution is to assess the variability of crime at the regional / district level in the Czech Republic between 2008 and 2016, to identify and characterize the districts with the highest crime rates. The state and development of crime is examined using the crime index, the crime structure is based on the tactical-statistical classification of the Police of the Czech Republic. At the regional level, the highest levels of crime are reported by the capital city of Prague, Ústí nad Labem Region and Moravian-Silesian Region, the safest being on the contrary in Zlín Region, Vysočina Region and Pardubice Region. Crime is further investigated at district level, from the calculated result order, ten districts with the highest rate of crime index were selected and analysed (Ostrava-City, Brno-City, Ústí nad Labem, Chomutov, Most, Teplice, Česká Lípa, Liberec, Kolín and Karviná). These districts are concentrated mainly in regions with high levels of crime. Depending on the structure, there is a dominant property crime, on the contrary, moral criminality is the least represented. The district of Ústí nad Labem is specific to the high level of crime committed by children and juveniles.
Regionální diferenciace kriminality v České republice
Keywords: regional development; regional disparities; regional security; criminality; crime index; regionální rozvoj; regionální disparity; bezpečnost regionu; kriminalita; index kriminality